2022
DOI: 10.3329/ralf.v9i1.59536
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of abundance and distribution of fish species in coast of Ghana, West Africa

Abstract: Marine fishes are currently experiencing population decline which has severe repercussions on food security, especially in fishing households. However, without assessing the distribution and abundance of these marine fishes, ensuring sustainable management will become impossible. Therefore, the study aimed at applying multivariate techniques to determine the biodiversity of fishes along the coast of Ahanta West, Ghana. Fish samples were collected daily through experimental fishing from November-December, 2011.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The mean of the 'D' reported by [33] was 0.04 which was lower than the mean of the 'D' obtained from the current study. Habitats with more interference, tend to have high 'D' (> 0.6), consisting of only one or a few species, and relatively large populations [22]. In this survey, the mean of the 'D' from the current study was 0.4 indicating a relatively stable habitat with less interference hence the composition of dominant species is relatively balanced and not dominated by only one (1) or two (2) particular species.…”
Section: Diversity Indicesmentioning
confidence: 49%
See 4 more Smart Citations
“…The mean of the 'D' reported by [33] was 0.04 which was lower than the mean of the 'D' obtained from the current study. Habitats with more interference, tend to have high 'D' (> 0.6), consisting of only one or a few species, and relatively large populations [22]. In this survey, the mean of the 'D' from the current study was 0.4 indicating a relatively stable habitat with less interference hence the composition of dominant species is relatively balanced and not dominated by only one (1) or two (2) particular species.…”
Section: Diversity Indicesmentioning
confidence: 49%
“…Based on the aforementioned studies findings from the current study were similar to that reported in other works. The reasons for the variation in findings in comparison to other studies could be a result of the following factors, environmental factors, time of sampling, sampling duration, depth and type of fishing gear, biological activities of fish species, geographical location, the possibility of tear of fishing gears and the intensity of fishing activities [22]. Concerning the environmental factors, [23] stated that human impact, however, has become a driving force in shaping the spatiotemporal patterns of species abundance and distribution through direct and indirect effects of fishing exploitation, climate change.…”
Section: Species Abundancementioning
confidence: 66%
See 3 more Smart Citations